Thriving For Success: Hadhrami Entrepreneurs’ Establishment in Diaspora, Evidence from Malaysia - Mubarak, Mohd Zain; Yaacob, Mohd Rafi; Abdul Razak , Ateerah (Journal of Population and Social Studies [JPSS], 2024)
Arabs of Hadhramaut are a subethnic group indigenous to the Hadhramaut region in South Arabia’s eastern Yemeni province. They are renowned for their reputation as successful businesspeople in Arabic countries and Southeast Asia, including Indonesia and Malaysia. This study investigates and unfolds what factors contribute to the success of Hadhrami entrepreneurs and how they are firmly embedded and merged to create a vibrant and competitive business. A score of Hadhrami entrepreneurs in Kelantan, Johor, and Penang were interviewed to get valuable information on the aim of the study. According to the study’s results based on a thematic analysis, familial education and environment play a significant role in fostering interest and encouraging Hadhramis to be involved in business. This factor was bolstered by personality traits such as self-reliance, the ability to recognize opportunities, tenacity, and self-assurance, as well as religious factors such as faith in the provision of sustenance, adherence to spiritual values such as honesty, trust, and responsibility as a Muslim entrepreneur. As far as Hadhrami entrepreneurs were concerned, the study concluded that a nexus of family upbringing factors, the right personality, and strong religious beliefs are paramount for their success.